Gambaran Diagnosa dan Tindakan Pada Pasien Poliklinik Fisioterapi di RSUD dr. H. Andi Abdurrahman Noor Tanah Bumbu - Muhammad Rizky; Aryadi Rachman; Mita Erliana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2025)
This study aims to provide an overview of the distribution of diagnoses and physiotherapy actions based on patient medical record data at the Physiotherapy Poly at RSUD dr. H. Andi Abdurrahman Noor Tanah Bumbu for the period January 2025. This study used descriptive quantitative method with retrospective approach and total sampling technique on 614 patients' medical record data. The results showed that the majority of patients were female as much as 56.51% and were in the age range of 36-55 years as much as 43.65%. There are 45 types of diagnoses with a total of 741 cases, the three most common diagnoses found are Osteoarthritis (23.89%), Low Back Pain (9.04%) and Hemiparese Sinistra (8.23%). Physiotherapy actions provided include exercise therapy (49.24%), TENS (23.19%), Infrared (12.56%), short wave diathermy (12.06%), injection (1.85%), Ultrasound (0.76%), and massage (0.34%). The results of this study provide an overview of the pattern of physiotherapy diagnosis and intervention, so that it can be used as a data-based reference to improve the effectiveness and quality of physiotherapy services in similar facilities.